When feelings obscure reason: The impact of leaders' explicit and emotional knowledge transfer on shareholder reactions - Nylund, Petra; Raelin, Jonathan (The Leadership Quarterly, 2015)
Emotions are an area of research commanding increasing scholarly attention in the field of leadership; yet, a focus on the cognitive processing of leaders has potentially obscured the impact that their emotions can have on shareholder reactions. Accordingly, this study contributes to extant theory by introducing the concept of emotional knowledge transfer, i.e., the emotional signals used for transmission and receipt of knowledge. Testable hypotheses are derived that explore the relationship between leader emotional and explicit knowledge transfer and shareholder reactions. A short-term event study is conducted across a sample of recorded CEO interviews and analyzed using random-effects regressions. Findings indicate that leaders' explicit and emotional knowledge transfer impact shareholder reactions negatively, and that leaders try to align emotional knowledge transfer with the explicit message they intend to convey. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Emotional displays; Knowledge transfer; Leadership; Event study